Two TonB-dependent outer membrane transporters involved in heme uptake in Anabaena sp. PCC 7120 - Julia Graf; Martin Schöpperle; Rafael Pernil; Enrico Schleiff (Microbial Cell, 2024)
Low availability of micronutrients such as iron has enforced the evolution of uptake systems in all kingdoms of life. In Gram-negative bacteria, outer membrane, periplasmatic and plasma membrane localized proteins facilitate the uptake of iron-loaded chelators, which are energized by TonB proteins. The specificity of different uptake systems likely depends either on the endogenously produced siderophore or on the bioavailability of iron-chelator complexes in the environment. Hence, an uptake system for schizokinen produced by the model cyanobacterium Anabaena sp. PCC 7120 exists, while bioinformatics analysis suggests the existence of additional systems, likely for uptake of xenosiderophores. Consistently, proteins encoded by alr2153 (hutA1) and alr3242 (hutA2) are assigned as outer membrane heme transporters. Indeed, Anabaena sp. PCC 7120 can utilize external heme as an iron source. The addition of heme resulted in an induction of genes involved in heme degradation and chlorophyll a synthesis and in an increase of the chlorophyll a content. Moreover, iron starvation induced the expression of hutA1, while the addition of heme led to its repression. Remarkably, the addition of a high concentration of heme but not iron starvation resulted in hutA2 induction. Plasmid insertion mutants of both genes exhibited a reduced capacity to recover from iron starvation by heme addition, which indicates a dependence of heme uptake on functional HutA1 and HutA2 proteins. The structural model generated by bioinformatics methods is further in agreement with a role in heme uptake. Thus, we provide evidence that Anabaena sp. PCC 7120 uses a heme uptake system in parallel to other iron acquisition systems.